Video on demand for Peer to Peer network - Waghchaure, Virangana; Chapte, Viresh (International Journal of Computer Sciences and Engineering, 2025)
In the proposed system a social-network-aided efficient P2P live streaming is performed, To prove that system outperforms other representative systems in terms of overhead, video streaming efficiency and server load reduction, and the effectiveness of the system two strategies. Reducing the cost of system in structure maintenance and node communication. The files can be moved from a centralized files to a decentralize server to distribute load and solve shutdown problems. Also cloud can be used for faster availability of files. Identity of peers in a private network remains hidden behind their global endpoint, P2P applications cannot run between two peers in separate private networks.